Uncorrected Tetralogy of Fallot with Pulmonary Atresia in an Asymptomatic 35 Year Old Nigerian Man - Areo, Olusegun, O.; Ajayi, Anthony, B.; Busari, Olusegun (International Journal of Innovative Research in Medical Science, 2018)
Tetralogy of Fallot is the commonest cyanotic congenital heart disease after the neonatal period, accounting for 10 - 26.2% of congenital heart diseases in Nigeria. Structural abnormalities found in tetralogy of fallot could explain associated adverse haemodynamic changes. It is imperative to document a case of an uncorrected tetralogy of Fallot with pulmonary atresia in a 35-year old Nigerian African man, considering the associated poor/high morbidity and mortality. Explanations for his longevity are left ventricular hypertrophy and systemic-pulmonary collateral circulation.